2016
DOI: 10.1186/s12934-016-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Sec signal peptide library from Bacillus subtilis for the optimization of cutinase secretion in Corynebacterium glutamicum

Abstract: BackgroundTechnical bulk enzymes represent a huge market, and the extracellular production of such enzymes is favorable due to lowered cost for product recovery. Protein secretion can be achieved via general secretion (Sec) pathway. Specific sequences, signal peptides (SPs), are necessary to direct the target protein into the translocation machinery. For example, >150 Sec-specific SPs have been identified for Bacillus subtilis alone. As the best SP for a target protein of choice cannot be predicted a priori, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 37 publications
(75 reference statements)
4
55
0
Order By: Relevance
“…Similar secretion performance was achieved when using the same SPs in closely related Bacillus species, namely B. subtilis and B. licheniformis (Degering et al, 2010). However, when comparing SPs for secretion of the same protein in more distantly related host organisms like B. subtilis and C. glutamicum, an erratic correlation of the secretion performance is found (Hemmerich, Rohe, et al, 2016).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Similar secretion performance was achieved when using the same SPs in closely related Bacillus species, namely B. subtilis and B. licheniformis (Degering et al, 2010). However, when comparing SPs for secretion of the same protein in more distantly related host organisms like B. subtilis and C. glutamicum, an erratic correlation of the secretion performance is found (Hemmerich, Rohe, et al, 2016).…”
mentioning
confidence: 59%
“…Application examples of cutinase comprise laundry and dishwashing detergents, food industry and textile processing (Chen, Su, Chen, & Wu, 2013). SPs from B. subtilis were shown to enable heterologous cutinase secretion in C. glutamicum (Rohe, Venkanna, Kleine, Freudl, & Oldiges, 2012), yet results from SP library screening in B. subtilis, to identify SPs causing high cutinase secretion efficiency in this organism, cannot be transferred to C. glutamicum (Hemmerich, Rohe, et al, 2016). Because it is not known that which SP is best suited to secrete cutinase with C. glutamicum for various bioprocess conditions a priori, five Sec SPs from B. subtilis were chosen, associated with a high (Epr), average (YwmC), and low (YpjP) cutinase secretion performance in B. subtilis (Brockmeier et al, 2006).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of MBR systems into robotic environments greatly enhances their capabilities towards an improved quantitative microbial phenotyping and bioprocess development . In particular, liquid handling robotics allow for automated manipulation of growing cultures, e.g., by adding inducers, taking samples, adding nutrients and adjusting pH.…”
Section: Microbioreactor (Mbr) Systemsmentioning
confidence: 99%
“…The less than optimal residue level fitness of wtVIM-2 may be because we employ E. coli as a host while natural VIM variants are often found in Pseudomonas 62 , and/or the signal peptide is not selected to produce maximum expression in natural environments. It has been shown that different signal peptides produce variable expression levels and translocation rates for a given protein, both of which affect the final resistance, especially in different host organisms 23,57,58,[63][64][65] . Furthermore, the signal peptide is frequently mutated in naturally occurring VIM-type variants (see section on 'Natural VIM variation' below), suggesting changes in the signal peptide sequences may have played significant roles in dissemination of MBL genes to different hosts and adaptation to higher antibiotic concentrations.…”
Section: Codon and Amino Acid Optimization In The Signal Peptidementioning
confidence: 99%